Traditional Fishing Gears and Fishing Methods Used in Koshi River Basin (Research Journal on Multi-disciplinary Issues, 2021)
The paper describes wide range of traditional fishing gears used by professional fishers in the Koshi River. It attempts to document the occurrence of 5 different kinds of commonly used gears, i.e. cast net, gill net, fish barrier, ghorleng, hook lines to catch fishes in different seasons in the lower middle stretch of the Koshi River. Among 5 different kinds of gears, hook line comes in recreational method while remaining ones viz. cast net, gill net, fish barrier, ghorleng are included under conventional method of fishing. The objective of study is to present the recent data of fishing methods, fishing gears and their distribution in different water bodies in the Koshi River. The primary data was collected through direct observation and secondary data through journals, books and interviews to local people. It was found that most of the fishing gears are made by locally available bio-degradable materials. It is supposed that this paper will support to the further researcher in their detail study on traditional fishing gears and for the conservation of local gears as well.